Hybrid Metaheuristic Algorithm for Job Scheduling on Computational Grids - Pooranian, Zahra; Shojafar, Mohammad; Tavoli, Reza; Singhal, Mukesh; Abraham, Ajith (Informatica)
Hybrid Metaheuristic Algorithm for Job Scheduling on Computational Grids